Method for high-value utilization of lithium smelting slag
By magnetic separation and hydrothermal pressing treatment of lithium smelt slag, and the dispersion of solutes such as oxalic acid solves the problem of difficult iron removal in lithium smelting slag, and efficient iron removal is achieved. The obtained elliptic-like products can be used for glass fiber raw materials, with low process cost and simple process.
Patent Information
- Application Number
- CN202510045842.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-11
- Publication Date
- 2025-04-25
AI Technical Summary
The existing ore dressing methods are difficult to effectively remove the iron present in lithium smelting slag, especially the iron is distributed in the silicate mineral phase, and conventional magnetic separation, flotation and other methods are difficult to remove.
After magnetic separation, the lithium smelting slag and the press-impregnated aqueous solution are used for water-heat pressing. The dispersion of solutes such as oxalic acid and sulfuric acid is used to reduce the sulfur and iron content of the lithium smelting slag, thereby obtaining iron-removed lecite-like materials.
Through this method, the iron content in the lithium smelting slag can be significantly reduced and the iron removal requirements can be met. The obtained elixir products can be used for glass fiber raw materials, and the process is low and the process is simple, which is suitable for post-industrialization.
Smart Images

Figure CN119873849A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of comprehensive utilization of solid waste, and in particular to a method for high-value utilization of lithium smelting slag. Background Art
[0002] In the context of energy transformation, the demand for lithium salts has greatly increased. In the new energy industry, more than 80% of lithium salts come from lithium ore. However, the existing lithium salt production process will produce a large amount of lithium smelting slag, resulting in a large accumulation of lithium slag solid waste, which seriously affects the ecological environment and occupies a large amount of land resources, greatly restricting the further development of the lithium salt industry. Therefore, finding a feasible way to recycle lithium smelting slag is crucial for the development of the industry and the protection of the ecological environment.
[0003] The main components of lithium smelting slag are silicon aluminum powder, and the total content of silicon dioxide and aluminum dioxide is greater than 73%, which is suitable for preparing silicon aluminum powder (basically the same as the elemental composition of pyrophyllite). The lithium smelting slag can be recycled and used in fillers, ceramic roasting materials, microcrystalline glass roasting materials and other fields. However, since the ceramic and other industries have strict requirements on the iron content of raw materials (Fe2O3≤0.6%), and the iron content of lithium smelting slag (in terms of Fe2O3) is generally around 1.4-2.5%. In addition, pyrophyllite, as a roasting raw material for ceramics, also has strict restrictions on sulfur content. When the SO3 content is greater than 2.5%, the scope and market value of lithium smelting slag will be greatly reduced. Therefore, desulfurization and iron removal to prepare qualified pyrophyllite products is an important prerequisite for the resource utilization of most lithium smelting slag. However, a considerable part of the iron in lithium smelting slag is distributed in the silicate mineral phase, which has weak magnetic properties and poor selectivity. Conventional mineral processing methods such as magnetic separation and flotation are difficult to remove iron from lithium smelting slag. Summary of the invention
[0004] The purpose of the present invention is to provide a method for high-value utilization of lithium smelting slag to solve the problem that existing mineral processing methods are difficult to remove iron in the mineral phase.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for high-value utilization of lithium smelting slag, comprising the following steps:
[0007] The lithium smelting slag is subjected to magnetic separation; the lithium smelting slag after magnetic separation is mixed with a pressure leaching aqueous solution, subjected to hydrothermal pressure leaching, and then subjected to solid-liquid separation to obtain a pyrophyllite-like material;
[0008] Among them, the active ingredients in the pressure soaking water solution include one or more combinations of oxalic acid, sulfuric acid, phosphoric acid, hydrochloric acid, nitric acid, sodium chloride, sodium sulfate, ammonium chloride, acetic acid, sodium bisulfate, sodium sulfite, potassium chloride, potassium nitrate, sodium nitrate, sodium acetate and potassium acetate.
[0009] Preferably, in the method for high-value utilization of lithium smelting slag, the particle size D of the lithium smelting slag is 50 10~45μm.
[0010] Preferably, in the method for high-value utilization of lithium smelting slag, the components of the lithium smelting slag include, by mass fraction: SiO2: 55-70%, Al2O3: 15-25%, SO3≤10%, Fe2O3: 1.4-2.5%, Li2O: 0.15-0.5%, Na2O+K2O: 0.5-3%.
[0011] Preferably, in the method for high-value utilization of lithium smelting slag, the magnetic field intensity of the magnetic separation is 1.5 to 3 T, and the number of magnetic separations is 1 to 3 times.
[0012] Preferably, in the method for high-value utilization of lithium smelting slag, the mass concentration of the active ingredient in the pressure leaching aqueous solution is 5 to 15%.
[0013] Preferably, in the method for high-value utilization of lithium smelting slag, the conditions for hydrothermal pressure leaching include: a solid-liquid mass ratio of 1:1 to 1:10, a pressure of 0.3 to 0.8 MPa, a temperature of 100 to 200°C, and a duration of 1 to 3 hours.
[0014] Preferably, in the method for high-value utilization of lithium smelting slag, the temperature of solid-liquid separation is 70-90°C.
[0015] Preferably, in the method for high-value utilization of lithium smelting slag, the components of the pyrophyllite material include, by mass fraction: SiO2: 55-80%, Al2O3: 15-25%, SO3: 0.1-1.0%, Fe2O3: 0.25-0.6%, Li2O≤0.13%, Na2O+K2O≤0.7%.
[0016] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:
[0017] (1) The method of the present invention utilizes an aqueous solution of one or more of the above solutes such as oxalic acid, sulfuric acid, sodium bisulfate, sodium bisulphite, potassium chloride, potassium nitrate, sodium nitrate, sodium acetate, potassium acetate, etc., which has a significant dispersing effect on sulfur-containing components such as calcium sulfate and iron components of lithium smelting slag, and can effectively reduce the sulfur content and iron content of lithium smelting slag, and the effect is better under the condition of pressure leaching. Its mechanism is mainly that the solute ions can effectively combine with iron ions and sulfur-containing components under the action of the crystal field, reduce the electron cloud energy, and promote the dissolution of iron under acidic conditions. Under the premise of lower material cost, the iron content in lithium smelting slag can be greatly reduced to meet the iron removal requirements, and the resulting pyrophyllite product can be used as a glass fiber raw material. Compared with other methods for removing iron from lithium smelting slag to prepare pyrophyllite-like component products, the method provided by the present invention has a high degree of iron removal and a high product qualification rate. Under the same quality of pyrophyllite-like products, the process cost of the present invention is lower, the raw materials are simple and easy to obtain, and the process is simple, which is conducive to the development of post-industrialization. It provides a more efficient solution for desulfurization and iron removal of lithium smelting slag to prepare pyrophyllite-like component products and then for resource utilization.
[0018] (2) During the hydrothermal pressure leaching deep iron removal stage, the lithium, sodium and potassium remaining in the lithium slag are also significantly leached out, further increasing the recovery rate of valuable metals and improving the economic efficiency of this technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the description of the embodiments or the prior art are briefly introduced below.
[0020] Figure 1 This is a flow chart of the high-value utilization method of lithium smelting slag. DETAILED DESCRIPTION
[0021] The present invention provides a method for high-value utilization of lithium smelting slag, comprising the following steps:
[0022] The lithium smelting slag is subjected to magnetic separation; the lithium smelting slag after magnetic separation is mixed with a pressure leaching aqueous solution, subjected to hydrothermal pressure leaching, and then subjected to solid-liquid separation to obtain a pyrophyllite-like material;
[0023] Among them, the active ingredients in the pressure soaking water solution include one or more combinations of oxalic acid, sulfuric acid, phosphoric acid, hydrochloric acid, nitric acid, sodium chloride, sodium sulfate, ammonium chloride, acetic acid, sodium bisulfate, sodium sulfite, potassium chloride, potassium nitrate, sodium nitrate, sodium acetate and potassium acetate.
[0024] In the present invention, the particle size D of the lithium smelting slag is 50 The thickness is preferably 10 to 45 μm, more preferably 20 to 40 μm, and still more preferably 30 to 35 μm.
[0025] In the present invention, when the particle size D of the lithium smelting slag is 50 When the requirement cannot be met, the lithium smelting slag is ground. The grinding conditions are not limited, as long as the particle size requirement is met.
[0026] In the present invention, the components of the lithium smelting slag preferably include, by mass fraction: SiO2: 55-70%, Al2O3: 15-25%, SO3≤10%, Fe2O3: 1.4-2.5%, Li2O: 0.15-0.5%, and Na2O+K2O: 0.5-3%.
[0027] In the present invention, the lithium smelting slag is preferably lithium smelting slag from which lithium is extracted and desulfurized, or lithium smelting slag that does not contain calcium sulfate.
[0028] In the present invention, the magnetic field strength of the magnetic separation is preferably 1.5-3T, more preferably 1.8-2.5T, and more preferably 1.8T; the number of magnetic separations is preferably 1-3 times, more preferably 2-3 times, and more preferably 2 times.
[0029] In the present invention, the active ingredients in the press-immersion aqueous solution preferably include one or more combinations of oxalic acid, phosphoric acid, hydrochloric acid, nitric acid, sodium chloride, ammonium chloride, acetic acid, sodium bisulphite, potassium chloride, potassium nitrate, sodium nitrate, sodium acetate and potassium acetate, and further preferably include one or more combinations of oxalic acid, phosphoric acid, hydrochloric acid, nitric acid, ammonium chloride, acetic acid, sodium bisulphite, potassium chloride and sodium acetate, and more preferably include one or more combinations of oxalic acid, hydrochloric acid, nitric acid, ammonium chloride and sodium acetate.
[0030] In the present invention, the mass concentration of the active ingredient in the pressure-immersion aqueous solution is preferably 5 to 15%, more preferably 10 to 15%, and even more preferably 12 to 14%.
[0031] In the present invention, the conditions for the hydrothermal pressure immersion include: the solid-liquid mass ratio is preferably 1:1 to 1:10, more preferably 1:4 to 1:8, and more preferably 1:5 to 1:6; the pressure is preferably 0.3 to 0.8 MPa, more preferably 0.5 to 0.7 MPa, and more preferably 0.55 to 0.6 MPa; the temperature is preferably 100 to 200°C, more preferably 135 to 165°C, and more preferably 160 to 165°C; the duration is preferably 1 to 3 hours, more preferably 1 to 2 hours, and more preferably 1 to 1.5 hours.
[0032] In the present invention, the temperature of the solid-liquid separation is preferably 70 to 90°C, more preferably 75 to 85°C, and even more preferably 80°C.
[0033] In the present invention, other conditions for the solid-liquid separation are not limited, and schemes well known in the art may be adopted.
[0034] In the present invention, the solid-liquid separation preferably further comprises: drying.
[0035] In the present invention, the drying temperature is preferably 100-130° C., more preferably 105-120° C., and more preferably 110° C.; the drying time is preferably 1-4 h, more preferably 1-2.5 h, and more preferably 1.5 h.
[0036] In the present invention, the composition of the pyrophyllite-like material preferably includes, by mass fraction: SiO2: 55-80%, Al2O3: 15-25%, SO3: 0.1-1.0%, Fe2O3: 0.25-0.6%, Li2O≤0.13%, and Na2O+K2O≤0.7%.
[0037] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Example 1
[0039] This embodiment provides a method for high-value utilization of lithium smelting slag, and the process is as follows: Figure 1 As shown, the following steps are included:
[0040] The pressure soaking solution is prepared by mixing phosphoric acid, sodium bisulfite and pure water in a mass ratio of 7:3:90;
[0041] Take 150g of lithium smelting slag, the composition of lithium smelting slag includes by mass fraction: SiO2: 67%, Al2O3: 23%, SO3: 2.0%, Fe2O3: 1.8%, Li2O: 0.25%, Na2O+K2O: 0.63%, the particle size of lithium smelting slag is D 50 =43μm, no grinding required; the lithium smelting slag was subjected to strong magnetic separation, the magnetic field strength was 1.8T, and the magnetic separation was repeated twice;
[0042] The lithium smelting slag after magnetic separation was added into 900g of press leaching water solution for slurry preparation, and the obtained slurry was subjected to hydrothermal press leaching. At this time, the solid-liquid mass ratio was 1:6, the press leaching pressure reached 0.6MPa, the temperature was 165°C, and the hydrothermal press leaching lasted for 1h. After the end, the solid-liquid separation was carried out at 80°C, and the obtained solid product was dried at 110°C for 1.5h to obtain pyrophyllite-like material.
[0043] The composition of the pyrophyllite material obtained in Example 1 is calculated by mass fraction, including: SiO2: 76%, Al2O3: 18%, SO3: 0.67%, Fe2O3: 0.50%, Li2O: 0.12%, Na2O+K2O: 0.6%. Relative to the original lithium smelting slag, the iron removal rate is greater than 70%, and the product composition meets the industry standard of pyrophyllite (the standard of pyrophyllite raw material used for glass fiber preparation: SiO2: 55-80%, Al2O3: 15-25%, SO3: 0.1-1.0%, Fe2O3: 0.25-0.6%, Li2O≤0.13%, Na2O+K2O≤0.7%).
[0044] Example 2
[0045] This embodiment provides a method for high-value utilization of lithium smelting slag, comprising the following steps:
[0046] Prepare a pressure soaking solution by mixing hydrochloric acid, ammonium chloride, sodium acetate and pure water in a mass ratio of 3:5:5:87;
[0047] Take 150g of lithium smelting slag, the composition of lithium smelting slag includes by mass fraction: SiO2: 69%, Al2O3: 23%, SO3: 2.35%, Fe2O3: 2.02%, Li2O: 0.15%, Na2O+K2O: 0.5%, the particle size D of lithium smelting slag 50 =63μm, grind for 30min to D 50 =38μm; the lithium smelting slag is subjected to strong magnetic separation, the magnetic field strength is 1.8T, and the magnetic separation is repeated twice;
[0048] The lithium smelting slag after magnetic separation was added into 900g of press immersion aqueous solution for slurry preparation, and the obtained slurry was subjected to hydrothermal press immersion. At this time, the solid-liquid mass ratio was 1:6, the press immersion pressure reached 0.55MPa, the temperature was 160°C, and the hydrothermal press immersion lasted for 1h. After the end, the solid-liquid separation was carried out at 70°C, and the obtained solid product was dried at 110°C for 2h to obtain pyrophyllite-like material.
[0049] The composition of the pyrophyllite-like material obtained in Example 2 is calculated by mass fraction, including: SiO2: 78%, Al2O3: 15.4%, SO3: 0.97%, Fe2O3: 0.42%, Li2O: 0.07%, Na2O+K2O: 0.47%. Relative to the original lithium smelting slag, the iron removal rate is greater than 75%, and the product composition meets the industry standard of pyrophyllite.
[0050] Example 3
[0051] This embodiment provides a method for high-value utilization of lithium smelting slag, comprising the following steps:
[0052] Prepare a pressure soaking solution by mixing oxalic acid and pure water in a mass ratio of 12:88;
[0053] Take 150g of lithium smelting slag, the composition of lithium smelting slag includes by mass fraction: SiO2: 64%, Al2O3: 25%, SO3: 1.5%, Fe2O3: 2.31%, Li2O: 0.34%, Na2O+K2O: 0.54%, the particle size of lithium smelting slag is D 50 =49μm, grind for 30min to D 50 =32μm; the lithium smelting slag is subjected to strong magnetic separation, the magnetic field strength is 1.8T, and the magnetic separation is repeated twice;
[0054] The lithium smelting slag after magnetic separation was added into 800g of press immersion water solution for slurry preparation, and the obtained slurry was subjected to hydrothermal press immersion. At this time, the solid-liquid mass ratio was 1:5.3, the press immersion pressure reached 0.55MPa, the temperature was 160℃, and the hydrothermal press immersion lasted for 1h. After the end, the solid-liquid separation was carried out at 90℃, and the obtained solid product was dried at 110℃ for 4h to obtain pyrophyllite-like material.
[0055] The composition of the pyrophyllite-like material obtained in Example 3 is calculated by mass fraction, including: SiO2: 76%, Al2O3: 17%, SO3: 0.45%, Fe2O3: 0.35%, Li2O: 0.11%, Na2O+K2O: 0.52%. Compared with the original lithium smelting slag, the iron removal rate is greater than 84%, and the product composition meets the industry standard of pyrophyllite.
[0056] Example 4
[0057] This embodiment provides a method for high-value utilization of lithium smelting slag, comprising the following steps:
[0058] Nitric acid and pure water are prepared into a pressure soaking solution in a mass ratio of 12:88;
[0059] Take 150g of lithium smelting slag, the composition of lithium smelting slag includes by mass fraction: SiO2: 64%, Al2O3: 25%, SO3: 1.5%, Fe2O3: 2.31%, Li2O: 0.34%, Na2O+K2O: 0.54%, the particle size of lithium smelting slag is D 50 =49μm, grind for 30min to D 50 =32μm; the lithium smelting slag is subjected to strong magnetic separation, the magnetic field strength is 1.8T, and the magnetic separation is repeated twice;
[0060] The lithium smelting slag after magnetic separation was added into 800g of press immersion water solution for slurry preparation, and the obtained slurry was subjected to hydrothermal press immersion. At this time, the solid-liquid mass ratio was 1:5.3, the press immersion pressure reached 0.55MPa, the temperature was 160℃, and the hydrothermal press immersion lasted for 1h. After the end, the solid-liquid separation was carried out at 85℃, and the obtained solid product was dried at 110℃ for 4h to obtain pyrophyllite material.
[0061] The composition of the pyrophyllite-like material obtained in Example 4 is calculated by mass fraction, including: SiO2: 77%, Al2O3: 16%, SO3: 0.40%, Fe2O3: 0.37%, Li2O: 0.10%, Na2O+K2O: 0.53%. Relative to the original lithium smelting slag, the iron removal rate is greater than 83%, and the product composition meets the industry standard of pyrophyllite.
[0062] Example 5
[0063] This embodiment provides a method for high-value utilization of lithium smelting slag, comprising the following steps:
[0064] Potassium chloride, acetic acid and pure water are prepared into a pressure soaking solution in a mass ratio of 4:10:86;
[0065] Take 150g of lithium smelting slag, the composition of lithium smelting slag includes by mass fraction: SiO2: 68%, Al2O3: 21.3%, SO3: 1.8%, Fe2O3: 1.5%, Li2O: 0.34%, Na2O+K2O: 0.73%, the particle size of lithium smelting slag is D 50 =39μm, no grinding required; the lithium smelting slag was subjected to strong magnetic separation, the magnetic field strength was 2.5T, and the magnetic separation was repeated 3 times;
[0066] The lithium smelting slag after magnetic separation was added into 900g of press leaching water solution for slurry preparation, and the obtained slurry was subjected to hydrothermal press leaching. At this time, the solid-liquid mass ratio was 1:6, the press leaching pressure reached 0.5MPa, the temperature was 155°C, and the hydrothermal press leaching lasted for 2h. After the end, the solid-liquid separation was carried out at 75°C, and the obtained solid product was dried at 100°C for 4h to obtain pyrophyllite-like material.
[0067] The composition of the pyrophyllite-like material obtained in Example 5 is calculated by mass fraction, including: SiO2: 75.6%, Al2O3: 17.3%, SO3: 0.80%, Fe2O3: 0.5%, Li2O: 0.11%, Na2O+K2O: 0.62%. Relative to the original lithium smelting slag, the iron removal rate is greater than 65%, and the product composition meets the industry standard of pyrophyllite.
[0068] Example 6
[0069] This embodiment provides a method for high-value utilization of lithium smelting slag, comprising the following steps:
[0070] Prepare a pressure soaking solution by mixing hydrochloric acid and pure water in a mass ratio of 15:85;
[0071] Take 150g of lithium smelting slag, the composition of lithium smelting slag includes by mass fraction: SiO2: 64%, Al2O3: 25%, SO3: 1.5%, Fe2O3: 2.31%, Li2O: 0.34%, Na2O+K2O: 0.54%, the particle size of lithium smelting slag is D 50 =49μm, grind for 30min to D 50 =32μm; the lithium smelting slag is subjected to strong magnetic separation, the magnetic field strength is 1.8T, and the magnetic separation is repeated twice;
[0072] The lithium smelting slag after magnetic separation was added into 800g of press immersion water solution for slurry preparation, and the obtained slurry was subjected to hydrothermal press immersion. At this time, the solid-liquid mass ratio was 1:5.3, the press immersion pressure reached 0.8MPa, the temperature was 135°C, and the hydrothermal press immersion lasted for 3h. After the end, the solid-liquid separation was carried out at 80°C, and the obtained solid product was dried at 110°C for 4h to obtain pyrophyllite material.
[0073] The composition of the pyrophyllite-like material obtained in Example 6 is calculated by mass fraction, including: SiO2: 73%, Al2O3: 15%, SO3: 0.54%, Fe2O3: 0.45%, Li2O: 0.12%, Na2O+K2O: 0.56%. Relative to the original lithium smelting slag, the iron removal rate is greater than 80%, and the product composition meets the industry standard of pyrophyllite.
[0074] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for high-value utilization of lithium smelting slag, characterized in that: The following steps are involved: The lithium smelting slag is subjected to magnetic separation; the lithium smelting slag after magnetic separation is mixed with a pressure leaching aqueous solution, subjected to hydrothermal pressure leaching, and then subjected to solid-liquid separation to obtain a pyrophyllite-like material; Among them, the active ingredients in the pressure soaking water solution include one or more combinations of oxalic acid, sulfuric acid, phosphoric acid, hydrochloric acid, nitric acid, sodium chloride, sodium sulfate, ammonium chloride, acetic acid, sodium bisulfate, sodium sulfite, potassium chloride, potassium nitrate, sodium nitrate, sodium acetate and potassium acetate.
2. The method for high-value utilization of lithium smelting slag according to claim 1, characterized in that: The particle size D of the lithium smelting slag 50 10~45μm.
3. The method for high-value utilization of lithium smelting slag according to claim 1 or 2, characterized in that: The components of the lithium smelting slag include, by mass fraction, SiO2: 55-70%, Al2O3: 15-25%, SO3≤10%, Fe2O3: 1.4-2.5%, Li2O: 0.15-0.5%, and Na2O+K2O: 0.5-3%.
4. The method for high-value utilization of lithium smelting slag according to claim 3, characterized in that: The magnetic field intensity of the magnetic separation is 1.5 to 3 T, and the number of magnetic separations is 1 to 3 times.
5. The method for high-value utilization of lithium smelting slag according to claim 1, characterized in that: The mass concentration of the active ingredient in the pressure soaking water solution is 5-15%.
6. The method for high-value utilization of lithium smelting slag according to claim 1, characterized in that: The conditions for the hydrothermal pressure immersion include: a solid-liquid mass ratio of 1:1 to 1:10, a pressure of 0.3 to 0.8 MPa, a temperature of 100 to 200° C., and a duration of 1 to 3 hours.
7. The method for high-value utilization of lithium smelting slag according to claim 1 or 6, characterized in that: The temperature of the solid-liquid separation is 70-90°C.
8. The method for high-value utilization of lithium smelting slag according to claim 1, characterized in that: The components of the pyrophyllite-like material include, by mass fraction, SiO2: 55-80%, Al2O3: 15-25%, SO3: 0.1-1.0%, Fe2O3: 0.25-0.6%, Li2O≤0.13%, and Na2O+K2O≤0.7%.
Citation Information
Cited By
Method for removing iron from spodumene smelting slag
CN120608204A